(untitled) (Al-Academy, 2023)
If the Industrial Revolution has enabled the replacement of humans with machines, the digital revolution is moving towards replacing our brains with artificial intelligence, so it is necessary to consider how this radical transformation affects the graphic design ecosystem. Hence, the research problem emerged (what are the effects of artificial intelligence on graphic design) and the research aimed to know the capabilities and effects of artificial intelligence applications in graphic design, and the study dealt in its theoretical framework with two main axes, the first is the concept of artificial intelligence, and the second is artificial intelligence applications in graphic design. The descriptive approach adopted a method of content analysis to analyze three research samples to reach a number of results and conclusions, including:1- Due to the employment of artificial intelligence in graphic design, it has facilitated the designer’s work in some routine design aspects and made him focus on the creative aspects of design more broadly.2- 2- As a result of the rapid scientific progress, the issue of creative awareness when applying artificial intelligence will be a temporary problem that can be overcome in the future and will accelerate the creative competition between it and the graphic designer